Children — The Last Minority Group - Muro, James J. (Canadian Journal of Counselling and Psychotherapy, 2012)
During the past decade, guidance counselors at all educational levels have pledged themselves to providing assistance to a diverse number of minority groups, ranging from the disadvantaged to the status of women. What we have perhaps neglected in our zeal to assist the less fortunate are the large number of "normal" children who daily file through the classrooms of our nation. Lacking the eloquent spokesmen of other movements, children are still being treated in many public schools as they were during the Industrial Revolution. What is desperately needed in public education is the development of increased numbers of spokesmen who will speak for this last great minority group. Numbered among these spokesmen should be the school counselor. The counselor can speak for and work toward the creation of schools where individual freedom and human dignity replace the shopworn curriculum as the key component of the educational process. In this context the counselor must become an active, doing individual who worries leas about his personal "role" and more about how children develop into healthy adults. He sheds the mantle of the isolated clinician, is active in the classroom, and uses his counseling skills to focus on assets rather than inadequacies. He views parents as partners in the educational scene, rather than as misdirected adults who badly need therapy. He is and must be a strong political force, for it is only through enlightened legislation that the last minority group will be served.